2007
DOI: 10.1002/14651858.cd004518.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Passiflora for anxiety disorder

Abstract: RCTs examining the effectiveness of passiflora for anxiety are too few in number to permit any conclusions to be drawn. RCTs with larger samples that compare the effectiveness of passiflora with placebo and other types of medication, including antidepressants, are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 16 publications
0
29
0
Order By: Relevance
“…There is a robust evidence-base for several herbal drugs such as St. Johns wort for depression or Echinacea for common cold [30, 31]. For some commonly used herbal drugs such as milk thistle or Passiflora, the evidence is contradictory or insufficient to draw conclusions [32, 33]. Regarding neural therapy, there are data proving the efficacy of the injection of local anaesthetics into trigger points, for example, in neck disorders [34].…”
Section: Discussionmentioning
confidence: 99%
“…There is a robust evidence-base for several herbal drugs such as St. Johns wort for depression or Echinacea for common cold [30, 31]. For some commonly used herbal drugs such as milk thistle or Passiflora, the evidence is contradictory or insufficient to draw conclusions [32, 33]. Regarding neural therapy, there are data proving the efficacy of the injection of local anaesthetics into trigger points, for example, in neck disorders [34].…”
Section: Discussionmentioning
confidence: 99%
“…Cochrane meta-analyses found two studies of passiflora (passion flower) indicating it was as effective as benzodiazepines (Level 2) [633], and one study of valerian which found no significant differences between placebo, valerian, or diazepam (Level 2, negative) [634,635]. Unfortunately, because these preparations are poorly standardized and have substantial variation in proportion of the active ingredient in different products, they cannot be widely recommended.…”
Section: Generalized Anxiety Disordermentioning
confidence: 99%
“…The plant is widely used in phytotherapy due to its mild sedative and anxiolytic properties [2,3]. Although some studies have demonstrated its anxiolytic properties [2,[4][5][6][7][8][9], two recent systematic reviews have emphasized that randomized controlled trials that compare the effectiveness of Passiflora with placebo or other types of medication are needed [10,11]. There is only one study in the literature that focuses on the anxiolytic effect of Passiflora incarnata Linneaus before general anesthesia [8], and there is no data on the preoperative oral administration of Passiflora incarnata Linneaus for anxiolysis before regional anesthesia.…”
Section: Introductionmentioning
confidence: 99%